Measurement of Antibiotic Consumption: A Practical Guide to the Use of the Anatomical Therapeutic Chemical Classification and Defined Daily Dose System Methodology in Canada - James M Hutchinson; David M Patrick; Fawziah Marra; Helen Ng; William R Bowie; Laurie Heule; Mark Muscat; Dominique L Monnet (Canadian Journal of Infectious Diseases)
Despite the global public health importance of resistance of microorganisms to the effects of antibiotics, and the direct relationship of consumption to resistance, little information is available concerning levels of consumption in Canadian hospitals and out-patient settings. The present paper provides practical advice on the use of administrative pharmacy data to address this need. Focus is made on the use of the Anatomical Therapeutic Chemical classification and Defined Daily Dose system. Examples of consumption data from Canadian community and hospital settings, with comparisons to international data, are used to incite interest and to propose uses of this information. It is hoped that all persons responsible for policy decisions regarding licensing, reimbursement, prescribing guidelines, formulary controls or any other structure pertaining to antimicrobial use become conversant with the concepts of population antibiotic consumption and that this paper provides them with the impetus and direction to begin accurately measuring and comparing antibiotic use in their jurisdictions.